PENGARUH PERBEDAAN UKURAN MATA PANCING DAN JENIS UMPAN PANCING SOGOK (HANDLINE) TERHADAP HASIL TANGKAPAN BELUT (Monopterus albus) DI RAWA PENING SEMARANG - Prasetiyo, Andi; Fitri, Aristi; -, Sardiyatmo (Journal of Fisheries Resources Utilization Management and Technology, 2012)
Fishing operations on eel (Monopterus albus) generally uses traps, handline and electrical fishing tools but in this research uses fishing gear called ‘pancing sogok’. ‘Pancing sogok is a fishing gear that consists of stick, line and a hook which operated by embedded on land and left in a night. The aim of this experiment were analyzed effects of size differences on hook (size 1 and 12), analyzed effects of bait differences on type (frog and worm) in Rawa Pening Semarang. The experimental method that used for this experiment was experimental fishing method with 2 variables, which is hook size and type of bait with 4 treatments. Data analysis used normality test and ANOVA test done with SPSS 16.0. The results showed that the differences between hook size number 1 and number 12 gave influences to the amount of eel catch (Monopterus albus). It’s showed by sig score hook size no.1 is 0,00 and sig score hook size no. 12 is 0,00 which both of them have sig score less than 0,05 and it meant H0 pushed away so it concluded that the hook size influenced the fishing catch. In other side, type of bait between frog and worm didn’t give influences on the amount of eel catch (Monopterus albus), it’s showed by sig score frog bait and worm bait which is 0,517 and 0,032 which both of them more than 0,05 and it’s meant H0 accepted. ANOVA test result showed that nothing interaction between hook size and type of bait.